Baseline socioeconomic characterization and resource use of the community in the Mefakiya watershed - Mohammed, Mekin; Bekele, Demsew; Bazie, Melkamu (Frontiers in Sustainable Food Systems, 2024)
Baseline characterization is used during the project to show progress toward the goal and objectives and after the project to measure the amount of change. The main objective of the study was to investigate the socio-economic characterization and natural resource use in the Mefakiya learning watershed. Both qualitative and quantitative data were collected. Quantitative data were collected using a structured questionnaire through face-to-face interviews with households at the intervention site. Sixty representative households were selected randomly and interviewed. Constraints and potentials were identified via focus group discussions. Descriptive statistics were used to analyze the quantitative data. The majority of the sample households (90%) were male-headed. Agriculture (crop and livestock production) is the principal (98.3%) occupation of the sample households in the Mefakiya watershed. Maize, finger millet, and teff, the major crops cultivated in the watershed, are produced by 98, 92, and 68% of the households, respectively. The study area is characterized by high natural resource degradation that is interconnected in nature. Therefore, an integrated approach is more important and necessary for the sustainable use of watershed resources and further development in all aspects of the watershed in the study area.